Dried blood spots to monitor the Anti-SARS-CoV-2 antibody response after infection or vaccination - Carthaus, A.; Görgens, C.; Knoop, A.; Geyer, H.; Thevis, M. (Deutsche Zeitschrift für Sportmedizin, 2022)
Summary: